Backhouse & Fontaine (eds.): A Historiography of the Modern Social Sciences - Duller, Matthias (Serendipities. Journal for the Sociology and History of the Social Sciences, 2016)
Book Review of: Backhouse, Roger E., and Philippe Fontaine, eds., A Historiography of the Modern Social Sciences Cambridge, New York: Cambridge University Press, 2014 pp. 248. ISBN: 978-1107037724 Price: $ 78.00